2022
DOI: 10.3389/fimmu.2022.818984
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Lactate-Related Prognostic Signature for Predicting Prognosis, Tumor Microenvironment, and Immune Response in Kidney Renal Clear Cell Carcinoma

Abstract: Kidney renal clear cell carcinoma (KIRC) is one of the most prevalent primary malignancies with high heterogeneity in the urological system. Growing evidence implies that lactate is a significant carbon source for cell metabolism and plays a vital role in tumor development, maintenance, and therapeutic response. However, the global influence of lactate-related genes (LRGs) on prognostic significance, tumor microenvironment characteristics, and therapeutic response has not been comprehensively elucidated in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 63 publications
2
45
0
Order By: Relevance
“…For example, dysregulations or polymorphisms of PER1, PER2, PER3, CLOCK, BMAL1, CRY1, CRY2, and NPAS2 were common in ovarian cancer, prostate cancer, leukemia, gliomas, hepatocellular carcinoma, and colorectal cancer [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In KIRC patients, bioinformatics methods found that the expression levels of some core clock genes were altered in correlation with the overall survival of patients [ 3 ]. However, there are few reports on the relationship between KIRC and other circadian genes in the circadian pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dysregulations or polymorphisms of PER1, PER2, PER3, CLOCK, BMAL1, CRY1, CRY2, and NPAS2 were common in ovarian cancer, prostate cancer, leukemia, gliomas, hepatocellular carcinoma, and colorectal cancer [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In KIRC patients, bioinformatics methods found that the expression levels of some core clock genes were altered in correlation with the overall survival of patients [ 3 ]. However, there are few reports on the relationship between KIRC and other circadian genes in the circadian pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney renal clear cell carcinoma (KIRC) is the most common histological subtype of renal cell carcinoma, accounting for 80–90% of all cases, with a high degree of immune infiltration [ 1 , 2 , 3 ]. A better understanding of the immune system and a discovery that tumors can take advantage of immune checkpoints to promote their survival and growth have resulted in the creation of immune checkpoint inhibitors (ICIs) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al demonstrated that the enhanced expression of four lactate risk-related genes, SLC25A3 , HPDL , NDUFA13 , and NARS2 , was correlated with poor prognosis in patients with skin cutaneous melanoma (SKCM), while patients with risk-related gene expression may benefit more from immune checkpoint inhibitor (ICI) therapy ( Xie et al, 2022 ). Sun et al established a lactate-related prognostic signature (LRPS) for the prognosis of patients with kidney renal clear cell carcinoma (KIRC) based on lactate metabolism-related genes and confirmed that LRPS might be effective in predicting the prognosis of patients with KIRC and that patients with low FPB1 and HDAH expression but high TYMP expression had a poor prognosis ( Sun et al, 2022 ). In our study, we found that STAT4 was an independent prognostic factor for BC in terms of both OS and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship between the risk score and expression of the immune checkpoints was investigated by Spearman's correlation analysis. In this study, the immunophenoscore (IPS) was used to evaluate the responses to anti-CTLA4 and anti-PD1 treatment regimens using The Cancer Immunome Atlas (TCIA, https://tcia.at/ ) database [ 37 ].…”
Section: Methodsmentioning
confidence: 99%